Effect of switching to erenumab in non-responders to a CGRP ligand antibody treatment in migraine: A real-world cohort study - Overeem, Lucas Hendrik; Lange, Kristin Sophie; Fitzek, Mira Pauline; Siebert, Anke; Steinicke, Maureen; Triller, Paul; Hong, Ja Bin; Reuter, Uwe; Raffaelli, Bianca (Frontiers in Neurology, 2023)
Background Therapeutic options for migraine prevention in non-responders to monoclonal antibodies (mAbs) targeting Calcitonin Gene-Related Peptide (CGRP) and its receptor are often limited. Real-world data have shown that non-responders to the CGRP-receptor mAb erenumab may benefit from switching to a CGRP ligand mAb. However, it remains unclear whether, vice versa, erenumab is effective in non-responders to CGRP ligand mAbs. In this study, we aim to assess the efficacy of erenumab in patients who have previously failed a CGRP ligand mAb. Methods This monocentric retrospective cohort study included patients with episodic or chronic migraine in whom a non-response (< 30% reduction of monthly headache days during month 3 of treatment compared to baseline) to the CGRP ligand mAbs galcanezumab or fremanezumab led to a switch to erenumab, and who had received at least 3 administrations of erenumab. Monthly headache days were retrieved from headache diaries to assess the ≥30% responder rates and the absolute reduction of monthly headache days at 3 and 6 months of treatment with erenumab in this cohort. Results From May 2019 to July 2022, we identified 20 patients who completed 3 months of treatment with erenumab after non-response to a CGRP ligand mAb. Fourteen patients continued treatment for ≥6 months. The ≥30% responder rate was 35% at 3 months, and 45% at 6 months of treatment with erenumab, respectively. Monthly headache days were reduced from 18.6 ± 5.9 during baseline by 4.1 ± 3.1 days during month 3, and by 7.0 ± 4.8 days during month 6 compared to the month before treatment with erenumab (p < 0.001, respectively). Responders and non-responders to erenumab did not differ with respect to demographic or headache characteristics. Conclusion Switching to erenumab in non-responders to a CGRP ligand mAb might be beneficial in a subgroup of resistant patients, with increasing responder rates after 6 months of treatment. Larger prospective studies should aim to predict which subgroup of patients benefit from a switch.